Effect of bis(triethoxysilylpropyl) tetrasulfide (TESPT) on properties of carbon nanotubes and conductive carbon black hybrid filler filled natural rubber nanocomposites - Y. Nakaramontri; C. Kummerloewe; N. Vennemann; S. Wisunthorn; S. Pichaiyut; C. Nakason (eXPRESS Polymer Letters)
Natural rubber (NR) and epoxidized natural rubber (ENR) vulcanizates reinforced by carbon nanotubes (CNT), conductive carbon black (CCB) and CNT/CCB hybrid filler without and with bis(triethoxysilylpropyl)tetrasulfide (TESPT) silane coupling agent were prepared using an internal mixer and a two-roll mill. Attenuated total reflection infrared spectroscopy (ATR-FTIR) was used to determine chemical interactions among rubber molecules, filler surfaces and silane molecules. In addition, the filler-filler interaction in NR and ENR matrices were assessed from wetting ability and Payne effect. Furthermore, the coupling by TESPT of filler surfaces and rubber molecules was clarified by temperature stress scanning relaxation (TSSR) technique. It was found that the rubber bound by physical absorption decreased with addition of TESPT, while the chemically bound amount significantly increased. This correlates well with estimates of physically and chemically bound rubber from swelling method and morphological properties. It was also found that the optimal electrical conductivity, percolation threshold concentration and dielectric constant of the composites were effectively improved by addition of TESPT. The improvement was confirmed by ANOVA. This indicates a great opportunity to manufacture smart materials with superior conductivity and dielectric constant, together with optimal scorch time, cure time and crosslinking properties.